Hypoxia Associated With Dihydropyridine Calcium Channel Inhibitors: A Pharmacovigilance Study in VigiBase - Chrétien, Basile; Decros, Jean Baptiste; Suard, Florimond; Dolladille, Charles; Fischer, Marc‐Olivier; Alexandre, Joachim; Descamps, Richard (Clinical Pharmacology & Therapeutics, 2023)
Due to their negative effects on hypoxic pulmonary vasoconstriction, dihydropyridine calcium channel inhibitors (DCCIs) can lead to hypoxia in patients with a pulmonary shunt. To date, only preclinical studies and case reports have focused on this potential adverse drug reaction. We aimed to assess the reporting association between DCCIs and hypoxia using the World Health Organization pharmacovigilance database (VigiBase). We performed a disproportionality analysis to evaluate the strength of the reporting association between i.v. clevidipine and nicardipine, thought to be a surrogate of patients in the intensive care unit, and hypoxia. The information component and the lower end of its 95% credibility interval were used to evaluate disproportionality. A description of the cases was made. Secondary outcomes included the association between all DCCIs and hypoxia compared with other treatments with similar indications, urapidil and labetalol, regardless of the route of administration. Association between oral nicardipine and hypoxia was also searched. A statistically significant signal of hypoxia was found for intravenous clevidipine and nicardipine. The time to onset was reported with a median of 2 days (interquartile range 1.5-4.5). Four dechallenges were performed with intravenous nicardipine, leading to the resolution of the symptoms. Regardless of the route of administration, a signal of hypoxia was also found for nimodipine but not for other drugs, including comparators. For nicardipine no signal of hypoxia was found with the oral route of administration. Our pharmacovigilance database analysis showed a significant association between the use of intravenous DCCIs and hypoxia.